The Implementation E-Government to Increase Democratic Participation: The Use of Mobile Government - Andi Fitri Rahmadany; Mansyur Ahmad (FISIP Universitas Islam Negeri Raden Fatah Palembang, 2021)
As information and technology develop the use of technology in various sectors has increased, including in the governance sector. Electronic governance was on the rise, especially with the limited mobility and social interaction restrictions during international health crises. Electronic government studies the use of information and communication technology within the public sector and holds the potentials of transformational government. The adoption of electronic governance in the public sector has created a revolution in the government’s administration and contributed to the improvement of accountability, efficiency, and transparency. The rationality of electronic governance is often associated with the increase of democratic participation through electronic government framework, involving a series of large-scale innovation projects and system that is technology-oriented. Through literature study, the researcher tried to analyze the implementation of electronic government to increase democratic participation through the use of mobile government by elaborating the functions electronic government can offers. The study reveals that electronic governance could provide open government data that opened a forum for citizens to debate over the issue concerning the government’s system that may solve several issues such as the low number of democratic participation and corruption.